2021
DOI: 10.3390/ijerph18126528
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Effects of Home Confinement and Social Distancing Derived from COVID-19 in the General Population—A Systematic Review

Abstract: (1) Background: Home confinement and social distancing are two of the main public health measures to curb the spread of SARS-Cov-2, which can have harmful consequences on people’s mental health. This systematic review aims to identify the best available scientific evidence on the impact that home confinement and social distancing, derived from the SARS-CoV-2 pandemic, have had on the mental health of the general population in terms of depression, stress and anxiety. (2) Methods: A systematic search was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
68
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 63 publications
1
68
1
6
Order By: Relevance
“…However, as previously mentioned, a problem with RT-PCRbased testing is the risk of long-term positivity in recovered patients without viable virus. Prolonged isolation of these patients has a great importance in terms of social, phycological, and economic consequences [18][19][20][21]. Moreover, these patients, despite being non-contagious, cannot access COVID-free healthcare facilities, and are at risk of re-infection, especially when new virus variants emerge, if admitted to COVID hospital wards.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as previously mentioned, a problem with RT-PCRbased testing is the risk of long-term positivity in recovered patients without viable virus. Prolonged isolation of these patients has a great importance in terms of social, phycological, and economic consequences [18][19][20][21]. Moreover, these patients, despite being non-contagious, cannot access COVID-free healthcare facilities, and are at risk of re-infection, especially when new virus variants emerge, if admitted to COVID hospital wards.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the correlation between RT-PCR results with viral cultures and contagiousness remains scarcely investigated [9]. The use of molecular detection of viral RNA implies the risk for many patients to remain hospitalized or isolated for a much longer time than necessary, with important implications for patient management, and also psychological, social, and economic consequences [18][19][20][21]. Therefore, availability of an accurate, rapid, and simple laboratory tool to certify the end of infectivity of SARS-CoV-2-infected patients would have a great impact.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies reveal alarming numbers: 69% of a study participants revealed clinically relevant anxiety, 31% depressive symptoms, and 20% significant post-traumatic stress symptoms [3], 30% of individuals have clinically significant levels of anxiety, depression, and stress [4]. Literature is not always clear on who are the most vulnerable, but it often reports women, young people, unemployed, and patients with prior mental or psychiatric illnesses [5]; another study found that symptoms of anxiety or depression and trauma were predicted by early age, presence of children at home and high estimates of personal risk; higher levels of anxiety and depression were also predicted by low income, loss of income and pre-existing health conditions in self and others, with specific anxiety levels about COVID-19 being Informatics 2021, 8, 51 2 of 17 higher in older participants [6]. A survey concludes that female gender, negative affect, and detachment were associated with higher levels of depression, anxiety, and stress; having an acquaintance infected was associated with increased levels of both depression and stress, whereas a history of stressful situations and medical problems was associated with higher levels of depression and anxiety; having a family member infected associated to higher levels of anxiety and having a family member who had to work outside their domicile associated to higher stress [7].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, over the last few years, the coronavirus disease 2019 (COVID-19) pandemic increased the rates of probable depression to two to nine times higher during the second wave than before the COVID-19 pandemic in Japan [ 9 ]. The COVID-19 pandemic is also a major problem for people’s psychological status all over the world, as mentioned in several review articles [ 10 , 11 ]. An accurate assessment of depression severity has become ever more important for its management in the general population.…”
Section: Introductionmentioning
confidence: 99%